2021
DOI: 10.3390/ijerph18179284
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Secondhand Smoke: Inconsistency between Self-Response and Urine Cotinine Biomarker Based on Korean National Data during 2009–2018

Abstract: This study aimed to estimate the secondhand smoke (SHS) exposure using urinary cotinine (UCo) to prove that the SHS exposure could not be properly assessed by self-reporting (SR). In total, 28,574 nonsmokers aged >19 years were selected from the Korean National Health and Nutrition Examination Survey data (2009–2018). First, changes in the annual concentration of UCo were analyzed, and the annual SHS exposure rates were measured based on SR and UCo from 2009 to 2018. Then, the average UCo concentration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…A low HPS assessed by the self-report does not necessarily mean less exposure to smoking in the home. Previous studies have revealed that SR does not reflect exposure at home fully 17 , 32 . Thirdhand smoke could happen in home without secondhand smoke, and homes are more vulnerable to long-term exposure to smoking materials, including thirdhand smoke, because people stay more at home than anywhere else 33 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A low HPS assessed by the self-report does not necessarily mean less exposure to smoking in the home. Previous studies have revealed that SR does not reflect exposure at home fully 17 , 32 . Thirdhand smoke could happen in home without secondhand smoke, and homes are more vulnerable to long-term exposure to smoking materials, including thirdhand smoke, because people stay more at home than anywhere else 33 .…”
Section: Discussionmentioning
confidence: 91%
“…However, exposure may occur in other areas, such as bars and sports facilities. Furthermore, NHANES in the US, including Korea, and population-based surveys mostly conduct interviews on indoor exposure 17 , 29 . Therefore, it is difficult for self-report to properly reflect exposure to smoking outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Regulations and social consensus for banning smoking in indoor public places and workplaces are becoming ubiquitous in recent years [6][7][8][9]. The consecutive Korean National Health and Nutrition Examination Survey (KNHANES) between 2008 and 2018 showed a trend toward significant decreases in self-reported tobacco smoke exposure and measured urinary cotinine concentrations [10][11][12]. Cotinine is a major metabolite of nicotine, and it is used as a biomarker for tobacco smoke exposure [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the globally declining trend of SHS, evidence on THS is limited. In a study in which Korean national data were used, Sim [18] reported that the SHS exposure rate among nonsmokers dropped by more than 80% since 2010 but that their cotinine concentrations did not considerably decrease. One possible reason for this phenomenon is THS.…”
Section: Introductionmentioning
confidence: 99%